2016
DOI: 10.1136/gutjnl-2016-311906
|View full text |Cite
|
Sign up to set email alerts
|

Full-spectrum (FUSE) versus standard forward-viewing colonoscopy in an organised colorectal cancer screening programme

Abstract: ISRCTN10357435.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 30 publications
0
53
2
2
Order By: Relevance
“…Miss rate of polyps has been shown to be substantially lower with full-spectrum endoscopy (FUSE) compared with standard forward-viewing (SFV) colonoscopy in a tandem study at per polyp analysis. However, there is uncertainty on whether FUSE is also associated with a higher detection rate of colorectal neoplasia, especially advanced lesions, in per patient analysis [24]. However, about 88.8% thought that early endoscopy contributes to the reduction of the complications of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Miss rate of polyps has been shown to be substantially lower with full-spectrum endoscopy (FUSE) compared with standard forward-viewing (SFV) colonoscopy in a tandem study at per polyp analysis. However, there is uncertainty on whether FUSE is also associated with a higher detection rate of colorectal neoplasia, especially advanced lesions, in per patient analysis [24]. However, about 88.8% thought that early endoscopy contributes to the reduction of the complications of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…All resected lesions, either by forceps or snare, were sent to pathology in separate jars and were processed and stained for histopathology using standard methods and evaluated by expert pathologists (one in each center) according to the Vienna criteria. 7,14 An advanced adenoma was defined as an adenoma >10 mm and/or with villous component > 20%, and/or high-grade dysplasia.…”
Section: Histopathologymentioning
confidence: 99%
“…4 The crossover design mitigates all such limitations, but it represents a fully artificial design, and it is also at high risk of operator bias, as the unblinded endoscopist performing the first procedure is aware of the subsequent colonoscopy to be performed. 4 When validating the same innovations with different study methodologies, inconsistent results have been frequently reported, [5][6][7][8][9] generating uncertainty as to how well the 2 study designs actually correspond.…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference in ADR between FUSE (43.6%) and standard forward view (45.5%). 43 Several other devices are available (mostly outside the US) to improve the field of view, and these generally result in an improvement in ADR by about 7%, but the cost of these devices precludes routine use. 34…”
Section: Fuse Regional Screening Program Of Fit-positive Patientsmentioning
confidence: 99%